Impact of Abattoir Waste on Water Quality and Public Health around Slaughterhouses in Jos Metropolis, Plateau State, Nigeria - Ibimode, Akinwumi A.; Laka, I. S.; Maton, S. M.; Ehada, I. D.; Maigida, G. T.; Ilenwabor, J. O.; Ukah, A. O.; Apagu, H. (Journal of Science Research and Reviews, 2024)
Water pollution occurs when harmful elements enter rivers, lakes, wells, streams, boreholes, or reserved freshwater sources in homes and industries. This study assesses the impact of abattoir waste on water quality in Jos metropolis, Nigeria. Two slaughterhouses were selected and data was collected through field surveys, interviews, and questionnaire administration to abattoir workers and residents living around the Abattoirs. Water samples were also collected from six wells near the abattoirs for physicochemical and bacteriological analysis. Simple descriptive statistics, the Chi-Square test and the Spearman Correlation Coefficient were applied to analyse the data collected. Results of water analysis from the laboratory show that all water samples collected do not fall within World Health Organization (WHO) permissible limits which is very critical to the wellbeing of the people living within the vicinity. Also, interviews and questionnaire results showed that abattoir wastes were discharged directly into the environment without proper treatment, thereby contaminating both surface and groundwater quality which residents depend on for domestic consumption. About 62% of the respondents depend on underground water source for their use. About 72% of respondents had observed changes in their water quality over the years, leading to diseases with typhoid at the fore. The Spearman correlation result reveals a strong and positive value of 0.664 at a p-value of 0.05 level of significance, which indicates a significant and positive relationship between abattoir waste and water quality. The X2 value of 91.654a and Asymptotic significance (2-sided) was less than 0.05 (0.011) also giving reason to retain the alternative hypothesis and conclude that there is a significant relationship between abattoir waste and water quality in Jos Metropolis slaughterhouses. The research suggests addressing abattoir waste and water contamination in Jos metropolis through stricter environmental regulations, water treatment facilities, operator training, and sustainable waste management practices.